An Orthodontic Retainer Preventing Remission in Celiac Disease. (November 2013) - Memon, Zebunnissa; Baker, Susan S.; Khan, Abdur; Hashmi, Humaira; Gelfond, Daniel
Celiac disease is a gluten enteropathy that is treated with dietary elimination of gluten. Exposure to nondietary sources of gluten, which are used in the manufacture of products such as plastics, dental equipment, and cosmetics, can also trigger or exacerbate disease. We report the case of a 9-year-old child who presented with nonspecific abdominal discomfort with abnormal serology for celiac disease. She underwent duodenal biopsies that revealed Marsh 3B histopathology. Despite strict dietary elimination of gluten, she continued to be symptomatic and demonstrate positive serum markers for active disease. It was then discovered that the child was exposed to gluten from her orthodontic retainer that contained a plasticized methacrylate polymer. Gluten is a common additive in plastics. She discontinued its use and demonstrated symptom resolution and complete normalization of serology. All possible sources of gluten, including nondietary, must be considered when managing a child with celiac disease.